EFEK MEDIASI TINGKAT KEPERCAYAAN PADA MANAJEMEN DAN REKAN KERJA DALAM POLA HUBUNGAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KEINGINAN UNTUK PINDAH (Studi Pada AJB Bumiputera Kebumen) - Elis Noer Shoimah (MNJ 16 UMY 307, 2016)
This research is aimed at identifying the effect of the level mediation of belief on the management and colleagues in the transformational leadership relations pattern toword to the turnover intentions on AJB Bumiputera Kebumen. The subject of the research is the manager and the agents of AJB Bumiputera Kebumen. In this research, the samples used are 100 respondents which are selected by using purposive sampling technique. The analysis instrument used is Double Linear Regression. Based on the analysis result, it is found that transformational leadership affects positively toward the belief to the management and colleagues, transformational leadership and belief affects negatively toward to the turnover intentions, and belief mediates the transformational leadership toward to the turnover intentions, and belief mediates the transformational leadership toward to the turnover intentions. Key words : Transformational Leadership, Belief toward the Management and